Increase in pulmonary blood flow at birth: role of oxygen and lung aeration. (10th September 2015) - Lang, Justin A.R.; Pearson, James T.; Binder‐Heschl, Corinna; Wallace, Megan J.; Siew, Melissa L.; Kitchen, Marcus J.; te Pas, Arjan B.; Fouras, Andreas; Lewis, Robert A.; Polglase, Graeme R.; Shirai, Mikiyasu; Hooper, Stuart B.
Abstract : Key points: There is no well‐established, direct correlation between local aeration and perfusion in the lungs immediately following birth. In a new study of simultaneous X‐ray imaging and angiography in near‐term rabbits, we investigated the relative contributions of lung aeration and increased oxygenation in the increase in pulmonary perfusion at birth. We demonstrated that partial lung aeration induces a global increase in pulmonary blood flow that is independent of changes in inspired oxygen. These results show that mechanisms unrelated to oxygenation or the spatial relationships that match ventilation to perfusion initiate the large increase in pulmonary blood flow at birth. Abstract: Lung aeration stimulates the increase in pulmonary blood flow (PBF) at birth, but the spatial relationships between PBF and lung aeration and the role of increased oxygenation remain unclear. Using simultaneous phase‐contrast X‐ray imaging and angiography, we have investigated the separate roles of lung aeration and increased oxygenation in PBF changes at birth using near‐term (30 days of gestation) rabbit kits ( n  = 18). Rabbits were imaged before ventilation, then the right lung was ventilated with 100% nitrogen (N2 ), air or 100% O2 (oxygen), before all kits were switched to ventilation in air, followed by ventilation of both lungs using air. Unilateral ventilation of the right lung with 100% N2 significantly increased heart rate (from 69.4 ± 4.9 to 93.0 ± 15.0 bpm), the diameters of both left and right pulmonary axial arteries, number of visible vessels in both left and right lungs, relative PBF index in both pulmonary arteries, and reduced bolus transit time for both left and right axial arteries (from 1.34 ± 0.39 and 1.81 ± 0.43 s to 0.52 ± 0.17 and 0.89 ± 0.21 s in the left and right axial arteries, respectively). Similar changes were observed with 100% oxygen, but increases in visible vessel number and vessel diameter of the axial arteries were greater in the ventilated right lung during unilateral ventilation. These findings confirm that PBF increase at birth is not spatially related to lung aeration and that the increase in PBF to unventilated regions is unrelated to oxygenation, although oxygen can potentiate this increase. Key points: There is no well‐established, direct correlation between local aeration and perfusion in the lungs immediately following birth. In a new study of simultaneous X‐ray imaging and angiography in near‐term rabbits, we investigated the relative contributions of lung aeration and increased oxygenation in the increase in pulmonary perfusion at birth. We demonstrated that partial lung aeration induces a global increase in pulmonary blood flow that is independent of changes in inspired oxygen. These results show that mechanisms unrelated to oxygenation or the spatial relationships that match ventilation to perfusion initiate the large increase in pulmonary blood flow at birth.